Occurrence and pattern of antibiotic resistance among dental plaque bacteria from gingivitis patients and their clinical correlation - Abdulaziz , Sazan M. (Journal of Baghdad College of Dentistry, 2018)
Background: A diverse group of bacteria live in biofilms in the oral cavity. On dental surfaces biofilms form plaque that is potentially involved in caries and periodontal diseases. Periodic studying of plaque microflora and their antimicrobial sensitivity patterns strongly affects the clinical practice in plaque-induced oral diseases.Materials and methods: Dental plaque samples were collected from 22 patients having ages ranged between 33 and 49 years with gingivitis that met the study criteria. Plaque, gingival and gingival bleeding indices (PI, GI, GBI) were measured for each patient. Laboratory procedures included microbiological examination of plaque samples followed by antibiotic sensitivity testing using disc diffusion method were also proceeded.Results: All patients were categorized as moderate gingivitis (GI: 1.1-2.0), the recorded PI were 1.2-2.7. Bleeding was observed in all subjects. Gingivitis was significantly higher in males (P=0.021). A total of 121 bacterial species were isolated from plaque samples, Facultative anaerobes constitute 83%. The most frequently isolated bacteria were Î±-hemolytic streptococci (36.36%) and Enterococcus faecalis (14.87%) among facultative, and Fusobacterium sp., Actinomyces sp., Veillonella sp. among obligate anaerobes (3.31%, 2.48%, 2.48%, respectively). Imipenem (77.2%) and Ciprofloxacin (59.4%) were the most effective agents against both bacterial groups. Multi-drug resistance (MDR) was recorded in most of the isolates (> 90%). A very highly significant relation between MDR with each of the above clinical criteria was recorded (P-value= 0.000).Conclusions: The high level of MDR isolates is of great clinical concern and requires an urgent reassessment of the policies of antibiotic prescription in dental settings.